The welfare effects of India’s rural employment guarantee - Klonner, Stefan; Oldiges, Christian (Journal of development economics, 2022)
We assess the welfare effects of India’s workfare program NREGA using a novel, almost sharp regression discontinuity design. We find large seasonal consumption increases in states implementing the program intensely, which are a multiple of the direct income gains. We also find increases in adolescents’ schooling. Our results imply substantial beneficial indirect effects of this large welfare program. We conclude that public employment programs hold significant potential for reducing poverty and insuring households against various adverse implications of seasonal income shortfalls — when properly implemented.
Available online 25 April 2022
Gesehen am 28.06.2022
Keywords: Indien